2020
DOI: 10.5114/hm.2021.98461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in adipocytokine concentrations and correlation between adipocytokines and body fat percentage after endurance training in obese girls

Abstract: Purpose. The purpose of the study was to evaluate changes in adipocytokine concentrations and the correlation between adipocytokines and body fat percentage after endurance training in obese girls. Methods. This was a semi-experimental study with a pre-test and post-test design, in which 19 overweight girls aged 8-12 years were randomly selected. Anthropometric and blood indices were assessed before and after the intervention. Results. The average leptin level (p = 0.016) and fat percentage (p = 0.002) were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, despite the benefits of exercise [13], most people, particularly obese people, find it difficult to practice, so walking is a simple, easy, and inexpensive way to exercise. Walking for 30 minutes three times a week is regarded as moderate exercise and can be used to reduce T2DM and depression [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the benefits of exercise [13], most people, particularly obese people, find it difficult to practice, so walking is a simple, easy, and inexpensive way to exercise. Walking for 30 minutes three times a week is regarded as moderate exercise and can be used to reduce T2DM and depression [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The primary risk factors for sarcopenia include a sedentary lifestyle, physical inactivity, chronic illness, hospitalization, taking certain medications, malnutrition, anabolic resistance, and decreased neuromuscular activation [5]. Physical activity and diet have been proven to be effective in preventing, managing, and treating chronic diseases, including hypertension, cardiovascular disease, age-related diseases such as sarcopenia, fatigue, and improved quality of life [7][8][9][10][11]. A review study conducted in 2017, which analyzed cross-sectional and cohort studies, found that increasing physical activity in the elderly reduces the risk of sarcopenia and its symptoms [12].…”
Section: Introductionmentioning
confidence: 99%